2021
DOI: 10.1016/j.ekir.2021.03.901
|View full text |Cite
|
Sign up to set email alerts
|

Data Challenges in Addressing Chronic Kidney Disease in Low- and Lower-Middle-Income Countries

Abstract: The burden of chronic kidney disease (CKD) is growing globally, particularly in low-and lower-middleincome countries (LLMICs) where access to treatment is poor and the largest increases in disease burden will occur. The individual and societal costs of kidney disease are well recognized, especially in developed health care systems where treatments for the advanced stages of CKD are more readily available. The consequences of CKD are potentially more catastrophic in developing health care systems where such res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Unexpectedly, sub-Saharan Africa with extremely poor life expectancies and little government health expenditure had the lowest ASIR from 1990 to 2019. The less advanced laboratory testing and unavailable data in many African countries might be responsible for the low “detected and reported” incident cases [ 21 , 22 ]. Therefore, it is important to raise the testing capacity and develop sustainable approaches to data measurement in these countries to discover the probably “masked” cases and develop more suitable prevention strategies in accordance with the real situation.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, sub-Saharan Africa with extremely poor life expectancies and little government health expenditure had the lowest ASIR from 1990 to 2019. The less advanced laboratory testing and unavailable data in many African countries might be responsible for the low “detected and reported” incident cases [ 21 , 22 ]. Therefore, it is important to raise the testing capacity and develop sustainable approaches to data measurement in these countries to discover the probably “masked” cases and develop more suitable prevention strategies in accordance with the real situation.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, nearly 95% of the published articles were authored by researchers from the top ten countries. Furthermore, a higher percentage of articles originated from developed nations (categorized by the World Bank) [32,33]. Notably, institutions in developed countries actively conducted research on the application of AI in the context of kidney disease [34].…”
Section: Discussionmentioning
confidence: 99%
“…Data registries are vital for understanding disease epidemiology, tracking progress and developing cost-effective intervention targets. Kidney disease registries are sparse in LICs and LMICs, which is where they are most needed 90 . A 2022 review of dialysis registries found none in large Asian countries 91 .…”
Section: Lack Of Health System Response To Kidney Disease and Global ...mentioning
confidence: 99%